What drives the high moments of hedge fund returns?. Issue 8 (13th February 2017) - Baker, H. Kent; Chkir, Imed; Saadi, Samir; Zhong, Ligang
ABSTRACT: We study the high-moment distribution of hedge fund returns and identify factors that drive high-moment risk. Using hedge fund monthly returns, we find a strong correlation between the first four moments of returns (i.e. mean, standard deviation (SD), skewness, and kurtosis) and different characteristics of the funds such as leverage, liquidity, incentives, and strategy-related factors. We find that after controlling for other factors, incentives-related factors and a hedge fund's specific strategy have the greatest impact on the distribution of fund returns. Our evidence also suggests investors allocate across hedge fund characteristics while placing greater emphasis on fund strategies and incentive factors.